The most beautiful bully - Freeman, Shannon (Shannon Ford) (Freeman, Shannon (Shannon Ford). Summit Middle School, 2015)
Seventh-grader Carson Roberts encounters drama when she starts at a new school and manages to cross bully Jessa McCain on her first day.